Analisis Penganggaran Modal Pekerjaan Perluasan Terminal Bandara Internasional Lombok PT. Angkasa Pura 1 (Persero) - Rivan Syamsurijal Biya; Rachmat Agus Santoso (Jurnal Riset Mahasiswa Akuntansi, 2023)
This study aims to analyze the budgeting process for the Expansion of Zainuddin Abdul Madjid Lombok International Airport Terminal at PT. Angkasa Pura 1 (Persero). The output of the final planning report will be analyzed using a comparative description method of aspects of company budgeting through the perspective of capital budgeting or investment, which is more project management or engineering system than investment in securities or others. The budgeting of Lombok International Airport Terminal Expansion Work from the search results has fulfilled some aspects of good corporate budgeting, although some strategic predictions missed expectations. The company's own capital budgeting in application and practicality there are several weaknesses in predicting future returns from the value of investments issued due to lack of integration with the company's strategic objectives or to top-level regulations that must be met, especially in the acquisition of asset values or fixed assets with significant value. With this paper, it is hoped that it can generate awareness of the importance of evaluating capital budgeting before the budget is issued to be tested for implementation from a value and time perspective.